1973
DOI: 10.1002/app.1973.070170112
|View full text |Cite
|
Sign up to set email alerts
|

Influence of shearing history on the properties of polymer melt. I.

Abstract: synopsisMelt flow behavior was examined using "as polymerized," mechanically intact polypropylene, and the same polymer after pelletization in a screw extruder. In addition, the polymers were extruded through different capillaries and subsequently tested for melt flow characteristics. Significant differences in shear stress a t a given shear rate and shear rate critical to the onset of extrudate roughness were found and compared with the previous shearing history. Both shearing intensity and mode of flow were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1975
1975
1987
1987

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…In addition to this effect, direct measurement of melt viscoSity in a cone and plate rheometer also indicated an increase in the melt viscosity after being recuperated from several cycles of processingm or simply, in an analogous teat, a considerable decrease in the melt flow index.21 Analogously, for the case of HDPE, a decrease has been reported in the melt index (or alternatively an increase in apparent viscosity) when samples with no previous shear history were melted and subjected to shear mixing. [22][23][24][25][26] All these evidences show that shear-induced changes in the melt rheological properties is a well documented phenomenon and that the shearing history indeed influences the polymer flow properties to a measurable and significant degree. In our case, which included the effect on HDPE and LDPE, it was found that particularly the same thermomechanical treatment had a more profound effect on the HDPE.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to this effect, direct measurement of melt viscoSity in a cone and plate rheometer also indicated an increase in the melt viscosity after being recuperated from several cycles of processingm or simply, in an analogous teat, a considerable decrease in the melt flow index.21 Analogously, for the case of HDPE, a decrease has been reported in the melt index (or alternatively an increase in apparent viscosity) when samples with no previous shear history were melted and subjected to shear mixing. [22][23][24][25][26] All these evidences show that shear-induced changes in the melt rheological properties is a well documented phenomenon and that the shearing history indeed influences the polymer flow properties to a measurable and significant degree. In our case, which included the effect on HDPE and LDPE, it was found that particularly the same thermomechanical treatment had a more profound effect on the HDPE.…”
Section: Resultsmentioning
confidence: 99%
“…(1) that mechanical and flow properties are not uniquely defined by the composition of these systems, but vary greatly with the degree of dispersion attained during the mixing process (2,3,4). In following the concepts of pertinent literature (2,3), this dependence on "shear history" can be attributed, at least partly, to the limited miscibility of the component polymers. Wetting and adhesion at interfaces of blend components is thereby limited, but may be improved by reducing the size of "domains" or of "stable molecular clusters" in the blend morphology.…”
Section: Introductionmentioning
confidence: 99%